Cyclic Peptide [R4W4] in Improving the Ability of First-Line Antibiotics to Inhibit Mycobacterium tuberculosis Inside in vitro Human Granulomas - Hernandez, Joshua; Ashley, David; Cao, Ruoqiong; Abrahem, Rachel; Nguyen, Timothy; To, Kimberly; Yegiazaryan, Aram; Akinwale David, Ajayi; Kumar Tiwari, Rakesh; Venketaraman, Vishwanath (Frontiers in Immunology, 2020)
Tuberculosis (TB) is currently one of the leading causes of global mortality. Medical non-compliance due to the length of the treatment and antibiotic side effects has led to the emergence of multidrug-resistant (MDR) strains of Mycobacterium tuberculosis (M. tb) that are difficult to treat. A current therapeutic strategy attempting to circumvent this issue aims to enhance drug delivery to reduce the duration of the antibiotic regimen or dosage of first-line antibiotics. One such agent that may help is cyclic peptide [R4W4], as it has been shown to have antibacterial properties (in combination with tetracycline) against methicillin-resistant Staphylococcus aureus (MRSA) in the past. The objective of this study is to test cyclic peptide [R4W4] both alone and in combination with current first-line antibiotics (either isoniazid or pyrazinamide) to study the effects of inhibition of M. tb inside in vitro human granulomas. Results from our studies indicate that [R4W4] is efficacious in controlling M. tb infection in the granulomas and has enhanced inhibitory effects in the presence of first-line antibiotics.